2022
DOI: 10.1088/1755-1315/1115/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

Tree diversity in Medan Ahmad Yani Park

Abstract: Medan is the capital city of North Sumatra Province. It is one of the biggest cities on Sumatra Island. Big cities in Indonesia generally have problems with environmental degradation. One of the efforts to preserve the environment in urban areas is to provide public green spaces. Ahmad Yani Park is a green space dominated by trees that grow compactly and tightly in 1.3 ha of area. The research has been conducted at Ahmad Yani Park, one of the favorite places for people to gather and enjoy the freshness of clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…However, considering that the study area comprised only two out of 56 sections, the sample collected was not adequate to represent the whole of Shah Alam city. Similar findings of medium diversity index were obtained in the city of Ahmad Yani Park, Medan, Indonesia with value of H' = 2.75 (Harahap et al 2022). In addition, the Shannon Evenness Index for the study area indicated value of 0.42 and 0.41 for Section 15 and Section 16, respectively.…”
Section: Species Diversity Richness and Evennesssupporting
confidence: 80%
“…However, considering that the study area comprised only two out of 56 sections, the sample collected was not adequate to represent the whole of Shah Alam city. Similar findings of medium diversity index were obtained in the city of Ahmad Yani Park, Medan, Indonesia with value of H' = 2.75 (Harahap et al 2022). In addition, the Shannon Evenness Index for the study area indicated value of 0.42 and 0.41 for Section 15 and Section 16, respectively.…”
Section: Species Diversity Richness and Evennesssupporting
confidence: 80%